Testing of Action of Direct Flame on Concrete. (19th February 2015) - Bodnarova, Lenka; Valek, Jaroslav; Novosad, Petr
Abstract : The paper states results of experimental exposition of concrete test specimens to direct flame. Concrete test specimens made from various mixtures differing in the type of aggregate, binder, dispersed reinforcement, and technological procedure were subjected to thermal load. Physicomechanical and other properties of all test specimens were tested before exposition to open flame: density, compressive strength, flexural strength, moisture content, and surface appearance. The specimens were visually observed during exposition to open flame and changes were recorded. Exposed surface was photographically documented before thermal load and at 10-minute intervals. Development of temperature of the specimens was documented with a thermocamera. After exposition to thermal load and cooling down, concrete specimens were visually observed, network of cracks was photographically documented, and maximal depth of spalled area was measured.